2020
DOI: 10.1016/j.pecs.2020.100842
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide poisoning and mitigation strategies for polymer electrolyte membrane fuel cells – A review

Abstract: Polymer electrolyte membrane fuel cells (PEMFC) have received much attention due to their high power density, good start-stop capabilities and high gravimetric and volumetric power density compared with other fuel cells. However, certain technological challenges persist, which include the fact that conventional anode electrocatalysts are poisoned by low levels (few ppm) of carbon monoxide (CO). This review considers the mechanism of CO poisoning and the effects that it has on the PEMFC performance. The key par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(71 citation statements)
references
References 217 publications
(386 reference statements)
0
71
0
Order By: Relevance
“…The oxidized product Zr-BTNDC-ox was obtained by stirring Zr-BTNDC in a solution of 30% H 2 O 2 aqueous solution for one day. 1 H NMR spectra confirmed that SCH 3 units were oxidized to sulfoxide or sulfone units. The PXRD pattern of the oxidized product is almost the same as that of Zr-BTNDC, indicating that the structure has not changed.…”
Section: Other Carboxylate-based Zr-mofsmentioning
confidence: 90%
See 2 more Smart Citations
“…The oxidized product Zr-BTNDC-ox was obtained by stirring Zr-BTNDC in a solution of 30% H 2 O 2 aqueous solution for one day. 1 H NMR spectra confirmed that SCH 3 units were oxidized to sulfoxide or sulfone units. The PXRD pattern of the oxidized product is almost the same as that of Zr-BTNDC, indicating that the structure has not changed.…”
Section: Other Carboxylate-based Zr-mofsmentioning
confidence: 90%
“…To solve these two problems, people hope to use more clean energy sources or new alternative energy such as fuel cells (FCs). 1 In this context, proton exchange membrane fuel cells (PEMFCs) are favoured by many researchers for their advantages of efficient energy conversion and nearly zero emission and so on. 2 In PEMFCs, a proton exchange membrane (PEM) provides a channel for proton transport, making protons pass across the film from the anode to the cathode, and forming a circuit with the electron transfer in the external circuit to provide current to the outside world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon corrosion and poisoning have been reported to be influential in the degradation and failure of the PEMFCs 148,149 …”
Section: Failure Modes Of Pemfc Componentsmentioning
confidence: 99%
“…146,147 Carbon corrosion and poisoning have been reported to be influential in the degradation and failure of the PEMFCs. 148,149 The system of carbon corrosion includes carbon reacting with water and producing carbon dioxide (CO 2 ).Though this reaction process infers that carbon is thermodynamically unstable to electrochemical carbon corrosion, the moderate energy of this response makes it conceivable to utilize carbon in PEMFCs. Nonetheless, irregular operating conditions, for example, the air/hydrogen boundary that occurs during the shut-down/ start-up operation at the anode, increment the cathode potential to a level higher than the open circuit voltage.…”
Section: Failure Modes Of Pemfc Componentsmentioning
confidence: 99%